Effectiveness of Pisang Raja Peel Extract (Musa Paradisiaca L) on Bacterial Growth of Porphyromonas Gingivalis as the Cause of Periodontitis - Andy Fairuz Zuraida Eva; Masriadi; Nur Rahmah Hasanuddin; Muhammad Ajis (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background. Periodontal disease is a chronic inflammatory infection that causes damage to thetissue supporting the teeth. The most common periodontal diseases are gingivitis and periodontitis.Periodontitis is a complex, localized chronic inflammatory disease characterized by the destruction ofconnective tissue, periodontal ligaments, and bone supporting teeth. This periodontal disease is causedby plaque bacteria on the surface of the teeth, where the plaque is a thin layer of biofilm containinga collection of pathogenic microorganisms such as Porphyromonas gingivalis, Actinobacillusactinomycetemcomitans, Prevotella intermedia, Tannerella forsythia and Fusobacterium nucleatumwhich are soft deposits. Porphyromonas gingivalis is a gram-negative, black pigmented, rod-shapedanaerobic bacteria. Porphyromonas gingivalis is one of the dominant bacteria in chronic periodontitiswhich is found in subgingival plaques. Indonesia is a country with a tropical climate which makesit rich in biodiversity, which can be used as antibacterial agents. Plantain (Musa Paradisiaca L) isa fruit that is easy to get, but the skin is rarely used. The Pisang Raja peel (Musa Paradisaca L)contains chemical compounds saponins, tannins, flavonoids, and alkaloids which have antimicrobialproperties. Objective: To determine the effectiveness of Pisang Raja peel (Musa Paradisiaca L) extractagainst the inhibition of Porphyromonas gingivalis bacteria as a cause of periodontitis. Methods: Usinglaboratory experimental methods, the test was carried out in the laboratory with the form of researchin the form of Posttest Only Control Design and sampling by random sampling through 4 treatmentsand 6 repetitions. Statistical test was One Way Anova. Results: Based on the oneway Anova test, theconcentration group of 16%, 32%, and 64% and the control group obtained a p-value of (p <0.01)which means that there is a significant difference. Conclusion: Based on the results of this study, it isshown that the effectiveness of Pisang Raja peel extracts concentrations with concentration 16%, 32%,and 64% in inhibiting Porphyromonas gingivalis bacteria and control group obtained p-value (p<0,01)means there was significant correlation. Conclusion: Based on this research that there is effectivecorrelation Pisang Raja peel extract with concentration 16%, 32%, dan 64% can inhibit the growthPorphyromonas gingivalis.